The effects of a translation training program on English as a foreign language trainees’ translation skills - Alolaywi, Yasamiyan (Frontiers in Education, 2022)
This study aimed to measure the effectiveness of a training experience involving a simulation of the work environment in developing the translation skills of a group of translation trainees. It also sought to investigate the participants’ views about their training experience as well as measure their level of satisfaction with the program. Thirty participants with qualifications in English language and translation from different regions of the Kingdom of Saudi Arabia participated in this study. This research is a quasi-experimental study in the form of a one-group pre-test and post-test design. Initially, the participants underwent a preliminary assessment (pre-test) of their translation abilities. Afterward, they undertook the experiment, an intensive course in translation and its required skills, which extended over a two-month period. At the end of the program, the participants underwent a post-test to measure whether there were statistically significant differences in their performance in the pre- and post-tests, with the results showing statistically significant differences in program performance (p. < .001). The data from the attitudinal questionnaire administered to the participants at the end of the program showed that they held positive opinions about the program and that they benefited significantly from the training experience. Based on these results, suggestions and recommendations are proposed to those interested in the field of training and translation and to further improve the work.